Plasma and amniotic fluid PPARγ is involved in the lipid metabolism of maternal–fetal interface cells. (18th October 2018) - Cheng, Yan; Liu, Shuangping; Lin, Ru; Wang, Jue; Peng, Ting; Zhang, Qingying; Cheng, Haidong
Abstract: Objectives: The aim of this study was at detecting the expression of peroxisome proliferator-activated receptor γ (PPARγ) in patients with gestational diabetes mellitus (GDM) and to investigate whether PPARγ regulates the lipid metabolism of maternal–fetal interface cells. Methods: We detected the expression of PPARγ in the maternal plasma, fetal plasma and amniotic fluid of two groups of women with GDM or normal pregnancy using ELISA and western blot. Establish the cell models of the indirect coculture model and the separate culture model using BeWo cells and endometrial stromal cells (ESCs). Oil red O staining was used to detect the lipid uptake, and the mRNA levels of the rate-limiting enzyme stearoyl CoA desaturase (SCD) and glucose transporter 1 (GLUT1) were detected by RT-PCR. Results: PPARγ is detectable in maternal plasma, fetal plasma and amniotic fluid. Levels of PPARγ in GDM maternal plasma were significant higher than other groups in vitro, with increasing PPARγ, the cytoplasmic lipid uptake levels of BeWo cells and ESCs were both increased in coculture conditions. GLUT1 and SCD mRNA rose significantly with increasing PPARγ in indirect coculture conditions, but both did not respond to PPARγ in ESC-absent culture conditions. Conclusions: The extracellular concentration of PPARγ may be involved in the lipid transport of maternal–fetal interface cells and may play a role in the abnormal lipid metabolism of GDM patients.